Social Media WOM: Definition, Consequences and Inter-relationships. (August 2014) - Ghosh, Angshuman; Varshney, Sanjeev; Venugopal, Pingali
Social media is the latest buzzword in the world of marketing and communication. Billions of people are using different social media sites on a daily basis. A significant proportion of consumers refer to reviews of products and services posted on social media before making their purchase decisions. In the process, the word of mouth or WOM messages posted by fellow users on social media sites play an important role. In this research article, we study how social media WOM influences the decision making of the recipient consumer. Based on study of the extant literature and consequent analysis, we present a set of research propositions and a conceptual model. The main relationships that we study are the impact of social media WOM on consumer purchase intention and brand attitude. We also study the role of key correlates in the context namely perceived risk, source credibility, social media website, perceived product knowledge and involvement level. The primary contributions of this research article are distinguishing the roles of positive and negative WOM, bringing WOM to the context of social media and studying the roles of key correlates.